MORPHOBIOLOGICAL CHARACTERISTICS OF THE GENUS BLAPS (COLEOPTERA: TENEBRIONIDAE) IN THE CENTRAL KYZYLKUM DESERT (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The Central Kyzylkum Desert is one of the largest desert regions, characterized by a sharply continental climate, high temperatures, and extreme moisture deficiency. Such harsh environmental conditions are clearly reflected in the morphological and biological adaptations of insect fauna, particularly in species belonging to the family Tenebrionidae (darkling beetles). Representatives of the genus Blaps Fabricius, 1775 constitute an important taxonomic group within the typical xerophilous entomofauna of the Kyzylkum Desert.